The Role of Al-Fatah Islamic Boarding School in Shaping Kampung Madinah in Temboro Karas Magetan - Rois, Muhammad Alfan Nur (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2023)
This study aims to analyze the role of Pondok Pesantren Al Fatah in constructing the socio-religious formation of “Kampung Madinah” in Temboro, Karas, Magetan. The research employed a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with pesantren leaders, community figures, students, and local residents, as well as documentation. Data validity was ensured through source and method triangulation. The findings reveal that Pondok Pesantren Al Fatah functions as an agent of social change through the internalization of Islamic values, the transformation of community religious practices, the reinforcement of modest dress culture, the habituation of congregational worship, and the development of a religiosity-based economic system. The pesantren operates not merely as a formal religious educational institution but also as a center of social engineering that shapes the collective habitus of the community toward an idealized socio-religious model referred to as “Kampung Madinah.” From the perspective of social change theory, the transformation process is gradual, cultural, and normative, occurring through mechanisms of value diffusion and role modeling. Within the framework of Islamic educational institution theory, the pesantren simultaneously performs educative, normative, and transformative functions. This study affirms the strategic capacity of pesantren as a religious institution capable of shaping social identity, cultural structure, and the moral orientation of society in a sustainable manner.